CULTURO-TECHNO-CONTEXTUAL APPROACH: SAMPLE IMPLEMENTATION STEPS FOR TEACHING SOCIOSCIENTIFIC ISSUES. - TEKİN, Nurcan; ASLAN, Oktay (Mehmet Akif Ersoy University Journal of Education Faculty, 2025)
The current study aims to evaluate, conceptualize, and provide a sample implementation of the culturo-techno-contextual approach (CTCA) on the basis of artificial intelligence as a socioscientific issue in teaching culture-based issues in science education. CTCA is a new approach, which has a conceptual history of only ten years, where culture, technology and context are handled in a pot. In this study, an exemplary implementation process for this approach, which may be suitable for socioscientific issues (SSIs) in terms of its local characteristic, was created. It is hoped that this sample implementation will provide a guiding framework for researchers in the teaching of SSIs, which have an important place in science education. In the study, the implementation steps are named to make it more usable for researchers. As CTCA is still a relatively new approach it is recommended that readers critically read these steps and detect possible shortcomings in the sample implementation and address them in new studies, if any.